Improving Chemistry Learning Outcomes in Redox Concept through Problem Based Learning for Tenth Graders at SMKN 2 Palembang - Hesti Rizki Amalia; Muhammad Hadeli; Rahma Aini (Pedagogy Review, 2022)
Abstract: This class action research aims to improve the learning outcomes of chemistry on students Grade X Geomatics 1 SMK Negeri 2 Palembang by implementing the Problem Based Learning model. This dtudy is conducted in two cycles, each cycle consist of two meetings. The data are obtained from using the observation sheet and students’ learning outcomes test which is given every meeting. The improvement of students’ learning outcomes can be observed from the average number of students’ learning outcomes before treatment (T0) in the amount of 68,97 with 38,23% learning completeness. The improvement happens on cycle I (T1) becomes 74,93 with the mastery 52,94% and on cycle II (T2) it increased to 85,79 with 88,23 % learning completeness. The application of Problem Based Learning model can improve learning outcomes. Keywords: class action research, problem based learning model, students’ learning outcomes of chemistry